Health Belief Model and Nursing Students' Perception about Benefits of Pre Conceptional Folic Acid Intake - Salma M. Mohamed; Galal A. Elkoly; Elham A. Ramadan; Soad A. Ramadan (Evidence-Based Nursing Research)
Context: Preconception folic acid intake is necessary for optimal embryogenesis. Using the health belief model is excellent to improve the young women's belief towards recommended healthy behaviors of taking folic acid.